PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KEMAMPUAN GERAK TARI MELAYU TRADISIONAL KELAS V SD NEGERI 37 PEKANBARU - Mitsalina Dalilah; Hendri Marhadi; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Dance is a human feeling about something that is explore through the beatiful rhythmic gestures. This research based on observation and documentation by a teacher of fifth grade. Can be concluded that the subjectsof dance is low and the teacher is not able to demonstrate the motion of malay dance correctly. The fore, condutstet a demonstration application of methot to enhance the capabilities of tradional malay dance. The purpose of this research to know whether the method of demonstration can be improve the ability of traditional malay dance motion. This research did on elementary scholl 37 Pekanbaru in fivth grade that numbered of 36 studens. Retrieval of data using observational techniques theacher and student activities and documentation. Known from primer data of this research about an average of 56,4 in the underprivileget categories. In cycle 1 about an average of 86,9 in the categorie capable. It shows that the method of demontration can be improve the ability of traditional malay dance motion.Keywords: Demonstration method, ability of dance motion